Influence of microstructure and hydrogen concentration on amorphous silicon crystallization - Budini, Nicolas (2010)
Hydrogenated amorphous silicon samples were deposited on glass substrates at different temperatures by high frequency plasma-enhanced chemical vapor deposition. In this way, samples with different hydrogen concentrations and structures were obtained. The transition from an amorphous to a crystalline material, induced by a four-step thermal annealing sequence, has been followed. Effusion of hydrogen from the films plays an important role in the nucleation and growth mechanisms of crystalline silicon grains. Measurements of hydrogen concentrations, Raman scattering, X-ray diffraction and UV reflectance showed that an enhanced crystallization was obtained on samples deposited at lower substrate temperatures. A correlation between these measurements allows to analyze the evolution of structural properties of the samples. The presence of voids in the material, related to disorder in the amorphous matrix, results in a better quality of the resulting nanocrystalline silicon thin films.